Evaluasi Program Kartu Prakerja: Apakah Program Ini Meningkatkan Upah Pekerja? (METODE DIFFERENCE IN DIFFERENCE)) - Nugraha, Muhammad Kivlan Reftreka; Ariyanto, Edi (Jurnal Ilmiah Akuntansi, Manajemen dan Ekonomi Islam (JAM-EKIS), 2025)
This study evaluates the impact of the Pre-Employment Card Program on workers' wage levels using SAKERNAS data. This study uses the Difference in Difference method to evaluate the pre-employment card program on wages. The results of the analysis show that the program has not succeeded in increasing workers' wages in accordance with its initial objectives. The results also show that workers who did not receive the pre-employment card have higher wage levels compared to those who received the program. These findings underscore the need for an in-depth evaluation of the design, implementation, and training curriculum of the Pre-Employment Card program. This evaluation should consider feedback from participants as well as a labour market needs analysis to ensure the program's relevance and effectiveness in increasing workers' wages in the future. This research also highlights the importance of adjusting the program based on dynamic labor market conditions as well as the specific needs of workers. The results of this study are expected to provide insights for policy makers and program implementers to improve the quality and impact of the Pre-Employment Card Program, so that it can contribute more effectively to improving the economic welfare of workers in Indonesia